2016
DOI: 10.1200/jop.2015.005751
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Oncology Unit Central Line–Associated Bloodstream Infections: Initial Results of a Simulation-Based Educational Intervention

Abstract: A targeted educational intervention using a simulated central line care model improved competence in central line care and resulted in decreased CLABSI rates for inpatient oncology patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…This scoping review revealed that ten studies used a single knowledge score to describe the state of nurses knowledge (Al Qadire, 2017; Alkubati et al., 2015; Barbosa et al., 2017; Dedunska & Dyk, 2015; Kelly, Green, & Hainey, 2015; Kurian & John, 2016; Letournel, 2018; Ozden & Caliskan, 2012; Paolucci, Nutter, & Albert, 2011; Raynak et al., 2018). Ten additional studies reported the effect of an educational intervention, using a pretest and post‐test design (Aloush, 2018; Aniyan & Shaiju, 2013; Banks,et al, 2010; Humphrey, 2015; Mutlu & Senturan, 2017; Ngo & Murphy, 2005; Page, Tremblay, Nicholas, & James, 2016; Roslien & Alcock, 2009; Yilmaz, Caylan, Aydin, Topbas, & Koksal, 2007; Xavier, 2013). Two authors tested nurses’ knowledge using a pre‐established minimum satisfactory score.…”
Section: Cvads—themes In the Literaturementioning
confidence: 99%
“…This scoping review revealed that ten studies used a single knowledge score to describe the state of nurses knowledge (Al Qadire, 2017; Alkubati et al., 2015; Barbosa et al., 2017; Dedunska & Dyk, 2015; Kelly, Green, & Hainey, 2015; Kurian & John, 2016; Letournel, 2018; Ozden & Caliskan, 2012; Paolucci, Nutter, & Albert, 2011; Raynak et al., 2018). Ten additional studies reported the effect of an educational intervention, using a pretest and post‐test design (Aloush, 2018; Aniyan & Shaiju, 2013; Banks,et al, 2010; Humphrey, 2015; Mutlu & Senturan, 2017; Ngo & Murphy, 2005; Page, Tremblay, Nicholas, & James, 2016; Roslien & Alcock, 2009; Yilmaz, Caylan, Aydin, Topbas, & Koksal, 2007; Xavier, 2013). Two authors tested nurses’ knowledge using a pre‐established minimum satisfactory score.…”
Section: Cvads—themes In the Literaturementioning
confidence: 99%
“…High-fidelity simulation might better improve competence in CVC care and decrease complications, as has been seen with nurses in oncology and intensive care units. 21,22 As the average LOS for this cohort was slightly >80 days, there would seem to be ample time for discharge teaching. However, the HPN team is necessarily involved throughout the entire course of the hospitalization.…”
Section: Discussionmentioning
confidence: 95%
“…For this population, there may be a steep learning curve faced when applying skills at home. High‐fidelity simulation might better improve competence in CVC care and decrease complications, as has been seen with nurses in oncology and intensive care units …”
Section: Discussionmentioning
confidence: 99%
“…Collaborative projects to reduce CLABSIs have been implemented in outpatient hemodialysis facilities and in oncology clinics. [3][4][5] However, a more comprehensive and coordinated approach is needed. 6 In particular, health care settings outside of acute care hospitals are severely under-resourced for surveillance activities.…”
Section: Discussionmentioning
confidence: 99%